Genetic variants for prediction of gestational diabetes mellitus and modulation of susceptibility by a nutritional intervention based on a Mediterranean diet - Ramos-Levi, Ana; Barabash, Ana; Valerio, Johanna; García de la Torre, Nuria; Mendizabal, Leire; Zulueta, Mirella; de Miguel, Maria Paz; Diaz, Angel; Duran, Alejandra; Familiar, Cristina; Jimenez, Inés; del Valle, Laura; et al. (Frontiers in Endocrinology, 2022)
Hypothesis: Gestational diabetes mellitus (GDM) entails a complex underlying pathogenesis, with a specific genetic background and the effect of environmental factors. This study examines the link between a set of single nucleotide polymorphisms (SNPs) associated with diabetes and the development of GDM in pregnant women with different ethnicities, and evaluates its potential modulation with a clinical intervention based on a Mediterranean diet. Methods: 2418 women from our hospital-based cohort of pregnant women screened for GDM (Jan2015-Nov 2017, SanCarlosCohort, RCT for prevention of GDM ISRCTN84389045 and RW study ISRCTN13389832) were assessed for evaluation. Diagnosis of GDM was made according to IADPSG criteria. Genotyping was performed by IPLEX MassARRAY PCR using Agena platform (AgenaBioscience,SanDiego,CA). 110 SNPs were selected for analysis based on selected literature references. Statistical analyses regarding patients’ characteristics were performed in SPSS (Chicago IL,USA,version24.0). Genetic association tests were performed using PLINK v.1.9,v.2.0 Bioinformatics analysis, with mapping of SNPs was performed using STRING,version11.5. Results: Quality controls retrieved 98 SNPs and 1573 samples, 272(17.3%) with GDM and 1301(82.7%) without . 1104(70.2%) were Caucasian and 469(29.8%) Hispanic. 415 (26.4%) were from the control group, 418(26.6%) from the nutritional intervention group, 740(47.0%) from the real-world group. 40 SNPs(40.8%) presented some kind of significant association with GDM in at least one of the genetic tests considered. The nutritional intervention presented a significant association with GDM, regardless of the variant considered. In Caucasian, variants rs4402960,rs7651090,IGF2BP2; rs1387153,rs10830963,MTNR1B; rs17676067,GLP2R; rs1371614,DPYSL5; rs5215,KCNJ1; rs2293941,PDX1 were significantly associated with increased GDM risk, whilst rs780094,GCKR; rs7607980,COBLL1; rs3746750,SLC17A9; rs6048205,FOXA2; rs7041847,rs7034200,rs10814916,GLIS3; rs3783347,WARS; rs1805087,MTR, were significantly associated with a decreased GDM risk. In Hispanic, variants significantly associated with increased risk of GDM were rs9368222,CDKAL1; rs2302593,GIPR; rs10885122,ADRA2A; rs1387153,MTNR1B; rs737288,BACE2; rs1371614,DPYSL5; and rs2293941,PDX1, whilst rs340874,PROX1; rs2943634,IRS1; rs7041847,GLIS3; rs780094,GCKR; rs563694,G6PC2; and rs11605924,CRY2 were significantly associated with decreased risk for GDM. Conclusions: We identify a core set of SNPs in their association with diabetes and GDM in a large cohort of patients from two main ethnicities from a single center. Identification of these genetic variants, even in the setting of a nutritional intervention, deems useful to design preventive and therapeutic strategies.